Functional hydrophobic coatings: Insight into mechanisms and industrial applications - Rahman, Atif Ur; Siti Maznah, Kabeb; Farah Hanani, Zulkifli (Elsevier Ltd., 2025)
Hydrophobic coatings have gained significant attention for their ability to enhance surface protection, corrosion resistance, and self-cleaning properties. However, achieving long-term durability and multifunctionality remains a critical challenge, requiring novel material engineering strategies. While previous studies have explored hydrophobic coatings, a comprehensive understanding of their synergistic nanomaterial interactions and industrial scalability is still lacking. This review fills this gap by providing an in-depth analysis of the fundamental mechanisms governing hydrophobic coatings, including wetting behavior, surface energy manipulation, and adhesion dynamics. A key focus is on the synergistic integration of graphene oxide (GO) and cellulose nanocrystals (CNC), demonstrating their combined effects on mechanical robustness, self-healing capabilities, and electromagnetic interference (EMI) shielding, properties essential for next-generation coatings. Furthermore, we examine emerging fabrication techniques such as liquid-phase polymerization and in-situ chemical precipitation, which optimize coating performance for real-world applications. Beyond material innovation, this review critically evaluates industrial applications across aerospace, marine, construction, and electronics, addressing key barriers to scalability, environmental sustainability, and regulatory compliance. By bridging nanomaterial engineering with functional surface modifications, this work offers a forward-looking perspective on the design of high-performance, sustainable hydrophobic coatings tailored for demanding industrial environments.